Experimental and theoretical investigation of the molecular and electronic structure of 5-(4-aminophenyl)-4-(3-methyl-3-phenylcyclobutyl)thiazol-2-amine - Ozdemir, Namik; Dincer, Muharrem; Cukurovali, Alaaddin; Buyukgungor, Orhan (Springer, 2009)
The title molecule, 5-(4-aminophenyl)-4-(3-methyl-3-phenylcyclobutyl)thiazol-2-amine (C20H21N3S), was prepared and characterized by H-1-NMR, C-13-NMR, IR and single-crystal X-ray diffraction. The compound crystallizes in the monoclinic space group P2(1)/c with a = 9.4350(5) , b = 11.2796(6) , c = 18.4170(8) and beta = 113.378(3)A degrees. In addition to the molecular geometry from X-ray experiment, the molecular geometry, vibrational frequencies, gauge including atomic orbital (GIAO) H-1- and C-13-NMR chemical shift values and atomic charges distribution of the title compound in the ground state have been calculated using the Hartree-Fock (HF) and density functional method (DFT) (B3LYP) with 6-31G(d) basis set. To determine conformational flexibility, molecular energy profile of the title compound was obtained by semi-empirical (AM1) calculations with respect to two selected degrees of torsional freedom, which were varied from -180A degrees to +180A degrees in steps of 10A degrees. Besides, frontier molecular orbitals (FMO) analysis was performed by the B3LYP/6-31G(d) method.
Keywords: Ab-initio calculation; AM1 semi-empirical method; B3LYP; Conformational analysis; Hartree-Fock; NMR spectroscopy; Vibrational assignment; X-ray structure determination